PENGGUNAAN METODE PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN KEMAMPUAN MENULIS MAHASISWA PROGRAM STUDI BAHASA INGGRIS FKIP UNIVERSITAS RIAU - Hadriana, Hadriana (Jurnal VARIDIKA, 2012)
This Research is aimed at finding out the level of writing ability of the students at English Study Program FKIP- UNRI by using Cooperative Learning Method. The samples of the research were all of the first year students that joined Writing IC. The procedure of the research were administered through (a) pre-tes; (b) teaching and learning process by using Cooperative Learning Method; and (c) pos-tes. Pre-tes and pos-tes were given in order to know the level of their writing ability. Data analysis was conducted by comparing the scores of pre-tes and post-tes. Data calculation concluded that with df = 78 ? 1 = 77, it was found that r table with significant level 5% = 2.64; and 1% = 1.99 which were smaller than t = 3.005. As a result, null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. In conclusion, Cooperative Learning Method played a significant role in increasing the writing ability of students of English Study Program FKIP UNRI.